Immune response to cold exposure: Role of γδ T cells and TLR2-mediated inflammation - Vasek, Daniel; Holicek, Peter; Galatik, Frantisek; Kratochvilova, Anna; Porubska, Bianka; Somova, Veronika; Fikarova, Natalie; Hajkova, Michaela; Prevorovsky, Martin; Zurmanova, Jitka M; Krulova, Magdalena (European journal of immunology, 2024)
The mammalian body possesses remarkable adaptability to cold exposure, involving intricate adjustments in cellular metabolism, ultimately leading to thermogenesis. However, cold-induced stress can impact immune response, primarily through noradrenaline-mediated pathways. In our study, we utilized a rat model subjected to short-term or long-term mild cold exposure to investigate systemic immune response during the cold acclimation. To provide human relevance, we included a group of regular cold swimmers in our study. Our research revealed complex relationship between cold exposure, neural signaling, immune response, and thermogenic regulation. One-day cold exposure triggered stress response, including cytokine production in white adipose tissue, subsequently activating brown adipose tissue, and inducing thermogenesis. We further studied systemic immune response, including the proportion of leukocytes and cytokines production. Interestingly, γδ T cells emerged as possible regulators in the broader systemic response, suggesting their possible contribution in the dynamic process of cold adaptation. We employed RNA-seq to gain further insights into the mechanisms by which γδ T cells participate in the response to cold. Additionally, we challenged rats exposed to cold with the Toll-like receptor 2 agonist, showing significant modulation of immune response. These findings significantly contribute to understanding of the physiological acclimation that occur in response to cold exposure.
Keywords: Animals; Acclimatization; zánět; hnědá tuková tkáň; Adipose Tissue, Brown; Cytokines; termogeneze; Toll-Like Receptor 2; Receptors, Antigen, T-Cell, gamma-delta; cytokiny; lidé; receptory antigenů T-buněk gama-delta; aklimatizace; Cold Temperature; T-lymfocyty; Inflammation; Thermogenesis; toll-like receptor 2; Male; krysa rodu Rattus; T-Lymphocytes; zvířata; mužské pohlaví; nízká teplota; Rats; Humans